OPTIMIZING INSTAGRAM AS A MEANS OF PROMOTION TO INCREASE CUSTOMER INTEREST IN UNIDA BARBERSHOP - Ihsan, Khozin Nur; Wahyudi, Amin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Instagram is one of the social media that is currently present in society. Instagram is currently also a promotional and advertising tool, the @u3_barber account is one of the accounts that uses Instagram social media as a promotional tool. The account contains various kinds of services and types of hairstyles. The purpose of this study is to analyze the use of Instagram as a promotional medium in spreading the content they have. This study uses a descriptive approach method with a qualitative research type. Data is collected by observation, interviews, and documentation which is defined as a problem-solving procedure that is investigated by describing or describing the state of the subject or object of research (a person, a company, etc.) at the present time based on facts that appear or as they are and the theory used is the promotion theory. The results of the study show that the use of Instagram social media as a promotional medium at Unida's Barbershop has a good impact on promotional activities through Instagram. The obstacles in using Instagram are the lack of ideas and preparation in carrying out promotional activities on Instagram. And the lack of utilization of the features available on Instagram. The solution to the obstacles is to further increase the creativity of ideas that can develop Unida's Barbershop and/or form a team to manage their Instagram accounts so that they can promote more actively. their product..